Incidence of PCT (plateletcrit) decrease in COVID-19 positive patients – diagnostic and epidemiologic value - Jevtić, Dalibor; Janković, Slavoljub; Marković, Danijela; Jevtić, Milena; Đorđević, Milan; Janković, Aleksa (General Practice, 2024)
Introduction: Platelets play an important role in the pathogenesis of COVID-19. Therefore, their parameters vary in different stages of the disease. The importance of plateletcrit in COVID-19 is not well known.Objective: To examine the diagnostic value of plateletcrit in COVID-19.Methods: From January to March and September-December 2021. during their initial visit to the COVID outpatient clinic at the Primary Healthcare Center Nis, we examined 440 patients who were experiencing possible COVID-19 symptoms. Following the examination, a complete blood count was performed, and they tested positive for COVID-19. We analyzed the plateletcrit in every lab sample collected duringtheir first visit. The control group consisted of 60 patients from the “green zone” from January to December 2021, as well as 48 patients from the pre-COVID period, before 2020.Results: Lower plateletcrit was found in 48,4% of women and 63,3% of men in the first period. Out of the total of 111 patients, lower plateletcrit was found in 54,9%. in the second period lower plateletcrit was found in 72,2% of women and 85% of men. Out of the total number of 329 patients, lower plateletcrit was found in 78,7%. In the controlgroup, from the “green zone” lower plateletcrit was found in 8,3% of 60 patients, and no decrease in plateletcrit levels was observed in 48 patients from the pre-COVID-19 era.Conclusion: Plateletcrit levels are decreased in many patients during their initial visit due to COVID-19. Symptoms. Therefore, variations in plateletcrit levels could raiseconcerns about potential COVID-19 infection
Keywords: platelets; infection; D-dimer,; virus